The Effects in Performance and Emissions of DI Diesel Engine Using Biodiesel (PPME)-Blends as Fuel - P. Venkateswara Rao (Asian Review of Mechanical Engineering, 2014)
In the present work biodiesel derived from non edible oil with diesel was used to study the performance of DI Diesel engine at 200 bar injection pressure and 1500rpm. Experiments were carried out with pogamia pinnata oil methyl ester (POME) and diesel blends in different proportions to reduce tail pipe emissions. Comparative study is conducted using diesel, biodiesel and with various blends of biodiesel. POME is used (diesel, 20, 40, 60, 80, 100) with various percentages by volume for all loads (0, 3, 6, 9 and 12kg load). The performance of the engine is compared with neat diesel in respect of brake thermal efficiency, BSFC and exhaust emissions.